2017
DOI: 10.1177/1179543317745863
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in Cycas (Cycadales: Cycadaceae) Species Offered as Larval Food Influences Fecundity of Chilades pandava (Lepidoptera: Lycaenidae) Adults

Abstract: Chilades pandava (Lepidoptera: Lycaenidae) larval food quality was studied to determine its influence on adult life history traits. A wild population from Cycas nongnoochiae (Cycadales: Cycadaceae) endemic habitat behaved similarly to the population collected from a garden setting. Cycas micronesica, Cycas revoluta, and Cycas seemannii leaves were used as high-quality food, whereas C nongnoochiae, Cycas taitungensis, and Cycas condaoensis leaves were used as low-quality food. The daily oviposition rate was not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 13 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…Luthrodes pandava herbivory pose a grave threat to cycad population (Marler & Muniappan 2006; Wu et al 2009, 2010; Marler et al 2012a,b, 2017; Fric et al 2014; Tennent, 2014; Whitaker & Salzman 2020). Insect herbivores such as Luthrodes pandava (previously Chilade s pandava ) present one of the primary threats to cycads.…”
Section: Introductionmentioning
confidence: 99%
“…Luthrodes pandava herbivory pose a grave threat to cycad population (Marler & Muniappan 2006; Wu et al 2009, 2010; Marler et al 2012a,b, 2017; Fric et al 2014; Tennent, 2014; Whitaker & Salzman 2020). Insect herbivores such as Luthrodes pandava (previously Chilade s pandava ) present one of the primary threats to cycads.…”
Section: Introductionmentioning
confidence: 99%
“…The cycads are facing threats posed by L. pandava such as deforestation, land transformation and shifting cultivation, etc., leading to habitat loss in ANI (Marler et al, 2012a(Marler et al, ,b, 2017. Marler et al (2017) reported that life history traits such as life span and fecundity play an important role in applied ecology and function of natural systems. More knowledge about life history traits of all trophic levels may be significant in conservation management of endangered host plant species.…”
Section: Introductionmentioning
confidence: 99%
“…Several cycads have been recorded as larval host plants for Luthrodes pandava (Amany et al, 2014; Chang, 1989; Chemnick & Gregory, 2010; Deloso et al, 2020; Feulner et al, 2014; Fric et al, 2014; Gao et al, 2004; Joo et al, 2008; Liu et al, 2003; Marler et al, 2012a,b, 2017; Marler & Muniappan 2006; Purti et al, 2022; Tennent, 2014; Whitaker & Salzman, 2020; Wu et al, 2009, 2010). Recently we had reported two endemic species of the genus Cycas viz.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations